Africa’s Natural Resource Wealth: A Paradox of Plenty and Poverty - Moti, Ukertor Gabriel (Advances in Social Sciences Research Journal, 2019)
Africa is blessed with vast natural resources and rich environments. It is generously endowed with productive land and with valuable natural resources, which include renewable resources (such as water, forestry, and ﬁsheries) and non-renewable resources (minerals, coal, gas, and oil). Natural resources dominate many national economies and are central to the livelihoods of the poor rural majority. These resources are the basis of income and subsistence for large segments of Africa’s population and constitute a principal source of public revenue and national wealth. Under the right circumstances, a natural resource boom can be an important catalyst for growth, development, and the transition from cottage industry to factory production. Indeed, with the right approach natural resources can be used to make the transformation from a low-value economy that relies on exports of primary commodities to one with a substantial labour-intensive manufacturing base. Ideally the development of these resources can be a blessing for the entire continent. But historically, those resources have often proved to be a curse than a blessing especially to the majority of the citizens in these African countries. It is commonly agreed that one of the avenues for getting many of the poorest African countries out of the low-income trap is to provide them with a big demand push that will generate enough demand complementarities to expand the size of markets and recover the ﬁxed costs of industrialisation. Natural resource wealth could be used to pursue this goal. Unfortunately, in many African countries natural resource booms have only to a limited extent set off a dynamic growth process. This is largely due to failure to implement the right growth promotion policies and to ensure that strong institutions are in place, suggesting that it is very difﬁcult to make the big push towards diversiﬁcation and development of manufacturing in the resource-rich parts of Africa. The danger is that much of Africa is not industrialised and is stagnating in a staple trap, dependent on exports of a few mineral resources. In particular, oil resources and other point resource-dependency could, with the wrong policies, lead to this scenario. The failure of natural resource wealth to lead to the expected economic growth and development has been attributed to several factors, including the so-called “Dutch Disease”, rent –seeking by elites, poor governance and weak institutions. The paper explores these causes of the resource curse and suggests ways to get out of the syndrome.